Efektivitas Pembelajaran Online Pasca Pandemi Covid-19 Pada Program Studi Teknik Informatika Sekolah Tinggi Teknologi YBS Internasional Tasikmalaya - Mia Sumiarsih; Rachmanto Hadiputranto; Raisman Hadi Hidayat; Hanif Insani (Journal on Education, 2023)
This research is Entitled The Effectiveness Of Online Learning After The Covid-10 Pandemic In The Informatics Engineering Study Program at Sekolah Tinggi Teknologi YBS Internasional. The purpose of this study is to determine the effectiveness of online learning after the covid-19 pandemic in the Informatics Engineering Study Program at Sekolah Tinggi Teknologi Ybs Internasional. This research is a quantitative descriptive study with a population of 15o students of the Informatics Engineering Study Program starting from class of 2018 to 2022 which is applied to the Odd Semester of the academic year 2022-2023. The number of sample amount 60 students and it was taken by using proportional stratified random sampling technique. The data coolection was obtained by distributing questionnaires using the assist of Google Form which consists of 21 statement items. The data analysis technique used is descriptive statistical analysis using a percentage calculation formula with the assist of Microsoft Office Excel. The result of the research shows that the Online Learning After the Covid-19 Pandemic in the Informatics Engineering Study Program was classified as effective. This can be seen from the quality learning indicator of 78,10%, the learning level compliance of 78,67%, the incentive of 77,80% and the time indicator of 82,44% with all average is 78,81% and it is categorized as efevtive.